Kazimieras Šaulys’s work Juodžiūnų tarmė (The dialect of Juodžiūnai):the first example of the systematic application of the IPA to a Lithuanian dialect - Bakšienė, Rima; Čepaitienė, Agnė (Baltistica, 2024)
This article examines the International Phonetic Alphabet (IPA) characters used for transcribing examples of the subdialect of the Eastern Aukštaitians of Kupiškis. The IPA characters used in the 1988 work Juodžiūnų tarmė (The dialect of Juodžiūnai) by Kazimieras Šaulys, a teacher, folklore collector, and dialect researcher, are compared with the current set of IPA characters used for the sounds of Lithuanian dialects.Additionally, the linguistic, socioeconomic, and sociocultural aspects of the traditional subdialect of Kupiškis as documented by Šaulys in the 20th century is contrasted with its current situation.The study underlines the value of Šaulys’s work and the data he collected for the science of dialectology, as has been emphasised by many linguists so far. An analysis of Šaulys’s chosen transcription is definitely useful for the development and improvement of the modern IPA system of Lithuanian dialects.
Keywords: Lithuanian dialects; Eastern Aukštaitians of Kupiškis; Kazimieras Šaulys; transcription; International Phonetic Alphabet; IPA